Size-assortative mating in simultaneous hermaphrodites: an experimental test and a meta-analysis - Graham, Stuart (2015)
Assortative mating by size has been argued to be widespread in the animal kingdom. However, the strength of size-assortative mating is known to vary considerably between species and the underlying mechanisms promoting this inter-specific variation remain largely unexplored. Size-assortative mating has been proposed to be particularly strong in simultaneous hermaphrodites, i.e. organisms that produce male and female gametes at the same time. Here, we build on this hypothesis by arguing that size-assortative mating mediated by sexual selection is generally stronger in reciprocally mating hermaphrodites compared with unilaterally mating species and separate-sexed organisms. We report a series of empirical tests suggesting that size-assortative mating in the unilaterally copulating freshwater snail Physa acuta is caused by spatial clustering of similar-sized individuals and not by mate choice. In addition, we present a meta-analysis testing, for the first time, the hypothesis that sexual selection-mediated size-assortative mating is stronger in reciprocally copulating simultaneous hermaphrodites. Overall, we found significant size-assortative mating across 18 tested species and substantial inter-specific variation. Importantly, part of this variation can be explained by mating type, providing support for the hypothesis that size-assortative mating is stronger in reciprocally mating hermaphrodites compared with unilaterally mating species. We highlight potential pitfalls when testing for sexual selection-mediated size-assortative mating and discuss the need for more experimental and comparative approaches in order to resolve the observed variation in the strength of size-assortative mating among species.